1985
DOI: 10.1021/bi00341a036
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence lifetime quenching and anisotropy studies of ribonuclease T1

Abstract: The time-resolved fluorescence of the lone tryptophanyl residue of ribonuclease T1 was investigated by using a mode-locked, frequency-doubled picosecond dye laser. The fluorescence decay could be characterized by a single exponential function with a lifetime of 3.9 ns. The fluorescence was readily quenched by uncharged solutes but was unaffected by iodide ion. These observations are interpreted in terms of the electrostatic properties of the amino acid residues at the active site of the protein, which would ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
40
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 46 publications
11
40
0
Order By: Relevance
“…Hence, it appears that this residue does not display detectable rapid motion on top of the overall rotational diffusion of the protein, which is in agreement with the recent observations of James et al (1985) using a picosecond laser and time-correlated single-photon counting.…”
Section: Anisotropy Decays Of Single Tryptophan Proteinssupporting
confidence: 90%
See 1 more Smart Citation
“…Hence, it appears that this residue does not display detectable rapid motion on top of the overall rotational diffusion of the protein, which is in agreement with the recent observations of James et al (1985) using a picosecond laser and time-correlated single-photon counting.…”
Section: Anisotropy Decays Of Single Tryptophan Proteinssupporting
confidence: 90%
“…7. In the absence of quenching (o) the intensity decay is closely fit by the single exponential model ( ), in agreement with James et al (1985) and of Eftink and Ghiron (1987 a). In the presence of 1.5 M acrylamide the single exponential model fails, as can be seen from the mismatch between the data (o) and the single exponential model, the systematic deviations, and the increase in ZzR from 0.97 to 52.8.…”
Section: Anisotropy Decays Of Single Tryptophan Proteinssupporting
confidence: 57%
“…Although the observation of homogenous fluorescence kinetics (monoexponential decay) in proteins is rare, it still is a reality. The well‐known examples are ribonuclease T1 at pH 5.5 (James et al 1985) and apoazurin (Huntik and Szabo 1989). Because of the ET‐quenching mechanism, heterogeneous fluorescence kinetics in proteins appears if ET process takes place in the time scale of fluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in a previous study aimed to estimate k ET in a model system where the donor and acceptor are separated by an increasing number of nonconjugated bridges, the authors concluded that, at short separating distances, k ET ≥ 10 11 s −1 , because no short‐lived fluorescence component occurred (Oevering et al 1987). Thus, if the fluorescence decay of RNT1 is monoexponential at pH 5.5 (James et al 1985) and biexponential at pH 7.4 (Table 1), it seems plausible that the change in ET rate with pH could be concerned. In studies of long‐distance ET in peptide models and proteins, it has been shown that at pH < 6, the ET rate increases (Weinstein et al 1991; Bobrowski et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, individual tryptophan residues have been found to display different emission maxima (Ross et al, 1981;Privat et al, 1980), which reflect the average polarity of their local environments. Additionally, time-dependent decays of fluorescence anisotropy have been used to detect segmental motions of tryptophan residues within proteins, as well as to detect overall rotational diffusion (Munro et a/., 1979;James et al, 1985;. In recent years the instrumentation has improved dramatically (Visser, 1985), so that events occurring in tens of picoseconds are now detectable (Nordlund and Podalski, 1983;Nordlund et a/., 1986;Ludescher et al, 1985;Wendler et al, 1986;Eichler et al, 1979;Lakowicz el al., 1986b and1987a).…”
Section: Introductionmentioning
confidence: 99%